Alleviating gender inequalities in Public Community Learning Centres in the Eastern Cape - Tawana, X.; Higgs, P. (South African Journal of Higher Education, 2021)
This article examines the problem of gender inequalities in Public Community Learning Centres in the Eastern Cape. It does so, to propose an alternative plan in which these centres might possibly help female adult learners reduce gender inequalities in everyday life in their communities. In short, the problem is: Public Community Learning Centres are mandated to advance equity and redress, and it is apparent that they do not in fact help or encourage communities to alleviate gender inequalities in the Eastern Cape. Determining why female adult learners do not take part in the in the economy of their communities will assist policy makers and these Public Community Learning Centres to come up with new initiatives that will address the needs and interests of female adult learners. This article was grounded on a Postcolonial Indigenous Paradigm which advocates for researcher accountability to the web of relations in which the research is conducted. Mixed Focus Groups discussions were conducted for adult learner participants to develop new understandings regarding gender relations as they interacted with each other around the theme of gender inequalities in their communities. Two Public Community Learning Centres located in a suburban and an inner city of the Eastern Cape were selected to conduct the research. The results of this study indicated that gender inequalities are present in closed doors and publicized bubbles in the Eastern Cape. In the light of this, and as a result of the research undertaken, recommendations are made to address the problem of gender inequalities in Community Learning Centres in the Eastern Cape.